Temperature effect on compression property of multiaxial warp-knitted composites. (May 2020) - Yang, Xiaori; Wang, Cong; Gao, Xiaoping; Zhu, Lvtao; Li, Yonggui
The wind turbine blades are exposed to various environments all the year round, especially temperature variations during the four seasons. To study the influences of temperatures on the mechanical properties of composite materials, the compression property in the 0°, 45°, and 90° directions of the multiaxial (triaxial and quadaxial) glass fiber warp-knitted composites at −30°C, 0°C, 20°C, and 40°C was analyzed, respectively. The stress–strain curves, strength, modulus, failure strain, and the relationship between strength and temperature were obtained. The results indicated that the compression performance decreased with the increase of temperature, and the effect of temperature on quadaxial composite was more significant than that of the triaxial composite. In addition, the failure mechanisms were also analyzed according to the fracture modes and scanning electron microscopic morphologies of composites.